Modified matrix solid phase dispersion-HPLC method for determination of pesticide residue in vegetables and their impact on human health: A risk assessment - Mujahid, Majida; Latif, Shoomaila; Ahmed, Mahmood; Shehzadi, Warda; Imran, Muhammad; Ahmad, Muhammad; Asari, Asnuzilawati; Jehangir, Muhammad; Mahmud, Zaid (Frontiers in Chemistry, 2022)
The use of pesticides is unavoidable in agricultural practices. This class of chemicals is highly toxic for the environment as well as for humans. The present work was carried out to assess the presence of some pesticides (diafenthiuron, lufenuron, azoxystrobin, difenoconazole, and chlorothalonil) residues in five of the very commonly used vegetables (eggplant, capsicum, apple gourd, cauliflower, and sponge gourd). Matrix solid phase dispersion (MSPD) technique was used to extract the pesticides and subsequently their quantification was performed through high performance liquid chromatography (HPLC) coupled to ultraviolet-visible (UV-Vis) detector. The elution was accomplished at wavelength of 254 nm by injecting 20 µL of standards or samples into chromatographic system. The mobile phase consisted of acetonitrile and water (80:20 v/v), where the flow rate was adjusted at 1.0 ml/min. The linearity was good (R2 ≥ 0.994) over a concentration range from 20 to 100 μg/ml for the investigated pesticides. The low detection limits showed a quite appreciable potential of the method to detect (1.12–1.61 μg/L) and quantify (3.73–5.36 μg/ml) the pesticides under study. The accuracy was demonstrated in terms of percent recovery which ranged between 88.5% and 116.9% for all the pesticides under investigation. These results justify the suitability of the technique for the intended purpose. The concentration of difenoconazole in apple gourd (20.97 mg/kg), cauliflower (10.28 mg/kg), and sponge gourd (40.32 mg/kg) whereas diafenthiuron in cauliflower (0.66 mg/kg) exceeded the maximum residue level (MRLs) as defined by Food and Agriculture Organization of the United Nations and the World Health Organization (FAO/WHO). Target hazard quotient (THQ) values of difenoconazole and diafenthiuron (except for adults) were more than one which indicates the significant effect on human health on consumption of apple gourd, cauliflower, and sponge gourd.